115k views
1 vote
Please help!! thank you.

Please help!! thank you.-example-1

1 Answer

3 votes

(A) Product of
-2x^(3)+x-5 and
x^(3)-3x-4 is:


(-2x^(3)+x-5)(x^(3)-3x-4)


=-2x^(3)(x^(3)-3x-4)+x(x^(3)-3x-4)-5(x^(3)-3x-4)


=(-2x^(3))(x^(3))+(-2x^(3))(-3x)+(-2x^(3))(-4)+x(x^(3))+(x)(-3x)+(x)(-4)+(-5)(x^(3))+(-5)(-3x)+(-5)(-4)


=-2x^(6)+6x^(4)+8x^(3)+x^(4)-3x^(2)-4x-5x^(3)+15x+20


=-2x^(6)+6x^(4)+x^(4)+ 8x^(3)-5x^(3)-3x^(2)-4x+15x+20


=-2x^(6)+7x^(4)+3x^(3)-3x^(2)+11x+20

(B) Yes.

Product of
-2x^(3)+x-5 and
x^(3)-3x-4 = Product of
x^(3)-3x-4 and
-2x^(3)+x-5 because multiplication is commutative.

Commutative Property of multiplication says that a.b = b.a.

Thus, multiplication is same irrespective of the order of two numbers.



User Permana
by
5.3k points